2016
DOI: 10.1371/journal.pone.0154225
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Telomeres in Schizosaccharomyces pombe and Its Possible Relationship to the Diversification of Telomere Binding Proteins

Abstract: Telomeres of nuclear chromosomes are usually composed of an array of tandemly repeated sequences that are recognized by specific Myb domain containing DNA-binding proteins (telomere-binding proteins, TBPs). Whereas in many eukaryotes the length and sequence of the telomeric repeat is relatively conserved, telomeric sequences in various yeasts are highly variable. Schizosaccharomyces pombe provides an excellent model for investigation of co-evolution of telomeres and TBPs. First, telomeric repeats of S. pombe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…The lengths of telomere arrays can also vary at the level of the species or ecotypes (reviewed in [22,23]). The human-type (TTAGGG) n telomeric sequence is conserved across several eukaryotic 'supergroups' [24], including the Amorphea supergroup with metazoan and fungal species (reviewed in [25,26]). At the same time, several exceptions are known across the Amorphea supergroup, e.g., in insects (TTAGG) n [27,28], in Nematodes (TTAGGC) n [29] or in several fungal genera, where very complex or irregular telomeric motifs were described [26,30] (Figure 2).…”
Section: The Origin Of Telomerasementioning
confidence: 99%
See 1 more Smart Citation
“…The lengths of telomere arrays can also vary at the level of the species or ecotypes (reviewed in [22,23]). The human-type (TTAGGG) n telomeric sequence is conserved across several eukaryotic 'supergroups' [24], including the Amorphea supergroup with metazoan and fungal species (reviewed in [25,26]). At the same time, several exceptions are known across the Amorphea supergroup, e.g., in insects (TTAGG) n [27,28], in Nematodes (TTAGGC) n [29] or in several fungal genera, where very complex or irregular telomeric motifs were described [26,30] (Figure 2).…”
Section: The Origin Of Telomerasementioning
confidence: 99%
“…The human-type (TTAGGG) n telomeric sequence is conserved across several eukaryotic 'supergroups' [24], including the Amorphea supergroup with metazoan and fungal species (reviewed in [25,26]). At the same time, several exceptions are known across the Amorphea supergroup, e.g., in insects (TTAGG) n [27,28], in Nematodes (TTAGGC) n [29] or in several fungal genera, where very complex or irregular telomeric motifs were described [26,30] (Figure 2). Additionally, the telomeres of some insects are constituted with unusual telomeric motifs, or even with telomeric repeats that consist of arrays of non-long-terminal-repeat (non-LTR) retrotransposons [31][32][33].…”
Section: The Origin Of Telomerasementioning
confidence: 99%
“…Candida albicans has longer, 23-nt tandem repeats that are overall GC-rich and contain a 5′-TGGTGT-3′; this arrangement is also found in other Candida species [65, 66] (Figure 2). The canonical tandem repeat in S. pombe is G 0-4 GGTTACAC 0-1 [67, 68], while the animal and human pathogens in the Taphrinomcyotina, Pneumocystis carinii and P. jirovecii , have telomere repeats composed of the more common 5′-TTAGGG-3′ sequence [69, 70]. Telomeres from Dikarya in classes outside of the Taphrinomycotina and Saccharomycotina were found to be 5′-TTAGGG-3′ repeats, like in N. crassa [71, 72] and A. nidulans [73, 74]; many additional species have been examined as part of genome sequencing projects (Figure 1), though many projects did not capture any telomere repeats, e.g.…”
Section: Chromosome Landmarks: Origins Telomeres and Centromeresmentioning
confidence: 99%
“…The situation is even more pronounced in species possessing heterogeneous telomeric repeats such as Saccharomyces cerevisiae and Schizosaccharomyces pombe . This poses a great challenge to TBPs, whose binding properties must rapidly co-evolve with their DNA targets (Steinberg-Neifach and Lue, 2015; Sepšiová et al, 2016; Červenák et al, 2017).…”
mentioning
confidence: 99%
“…Over the past few years this question has been addressed through biochemical and genetic analysis of TBPs from various yeast species (Kramara et al, 2010; Lue, 2010; Visacka et al, 2012; Steinberg-Neifach and Lue, 2015; Sepšiová et al, 2016; Červenák et al, 2017). Our studies have shown that Tay1, the dsTBP of the yeast Yarrowia lipolytica (Kramara et al, 2010) exhibits lower affinity for its own telomeres than for the mammalian-type telomeric repeats (Table 1).…”
mentioning
confidence: 99%